"Sarcocornia hispanica" ("Chenopodiaceae"), a new species from the Iberian Peninsula - de la Fuente, Vicenta; Rufo Nieto, Lourdes; Sánchez-Mata, Daniel (Lazaroa, 2011)
A new hexaploid species of Sarcocornia A.J. Scott, S. hispanica, is described from south east territories of the Iberian Peninsula as a new species. The micro-, macromorphological and cytological features of this taxon are given.